Indian Journal of Orthopaedics - Maini, Lalit; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer.)
IJO welcomes articles that contribute to Orthopaedic knowledge from India and overseas. We publish articles dealing with clinical orthopaedics and basic research in orthopaedic surgery. Articles are accepted only for exclusive publication in the Indian Journal of Orthopaedics. Previously published articles, articles which are in peer-reviewed electronic publications in other journals, are not accepted by the Journal. Published articles and illustrations become the property of the Journal. The copyright remains with the journal. Studies must be carried out in accordance with World Medical Association Declaration of Helsinki.
Keywords: Orthopedics; Orthopedics; Surgical Orthopedics; Conservative Orthopedics